Hanok: architecture in harmony with nature (2015)
This article aims to facilitate an approach to Korean culture through the description of the traditional Hanok architecture and point out its special consideration and use of the natural environment to adapt it to the needs of those who inhabit it. Hanok is the term used to refer to a house built in the traditional Korean architectural style that is characterized by the use of natural materials such as wood, paper, mud and stones; and for their constructive processes that achieve a type of ecological housing whose most significant features had and continue to have influence in more recent schools of architecture. Also the Hanok is a type of construction that exemplifies some values present in the Korean tradition such as Confucianism and Taoism.